New high yielding rice variety for irrigated ecology released in Madagascar (FOFIFA 188) - CGIAR Research Program on Rice (2020)
High yielding and acceptable grain quality germplasm released by the National Varietal Release Committee (SOC). Breeder and foundation seeds are delivered and certified seed has been produced.